Assessing the Economic Value and Credit Market Potential of Carbon Stock in South Nandi Forest, Kenya - Gibson , Mwatete; Joel , Sumukwo (African Journal of Education,Science and Technology (AJEST), 2017)
Provision of information about carbon stock and potential carbon market for tropical forests ecosystem is an important knowledge base, which is scarce in developing countries, for decision making in carbon trade. Financial benefits of the carbon market, which has not been developed before, in which this study focuses would not only lead to poverty alleviation among local communities but also serve as an incentive for better management of the forest ecosystem. This study aimed at assessing the economic value of carbon stock in South Nandi forest towards securing its credit market for the forest adjacent communities. South Nandi forest is among the few remaining tropical rainforests in western Kenya, and it is a major source of livelihoods for forest adjacent communities. This protected ecosystem hosts a variety of endangered plants, animals and endemic bird species. This study comprised of two forest surveys: Participatory Forest Resource Assessment (PFRA) and carbon assessment survey. Results indicated a total carbon store of 2.8 ± 0.8 million tons of carbon (equivalent to 10.5 ± 2.9 million tons CO2). The findings showed that more open forest areas had lower carbon densities. The study found that there was potential for tree planting projects in and around the South Nandi Forest to attract carbon funding either through the regulated carbon credit market under the Clean Development Mechanism (CDM) or through the voluntary carbon market. One option would be to reforest degraded or cleared areas within the forest boundaries with indigenous species. Tree planting projects outside of the forest boundary, such as trees planted on farms, could apply for carbon based funding depending on their management. Activities that reduce deforestation in the South Nandi Forest could also attract REDD (Reduced Emissions from Deforestation and Degradation) project funding.